Photosynthetic Mechanisms of Metaxenia Responsible for Enlargement of Carya cathayensis Fruits at Late Growth Stages - Huang, Ren; Zhang, Yun; Zhang, Qixiang; Huang, Jianqin; Hänninen, Heikki; Huang, Youjun; Hu, Yuanyuan (Frontiers in Plant Science, 2020)
Fruits of hickory (Carya cathayensis) are larger and their peel is greener after interspecific pollination by pecan (Carya illinoinensis; later pp fruits) than after conspecific pollination by hickory (later ph fruits). Previous studies have found little genetic differences between offspring and their maternal parent, indicating that the observed trait differences between pp and ph fruits are due to metaxenia. Fruit development depends on the amount of photosynthetic assimilate available. Since there is no difference in photosynthesis of the associated leaves between pp and ph fruits, the larger size of the pp fruits might be attributed to changes in fruit photosynthesis caused by the different pollen sources. To elucidate to the photosynthetic mechanisms behind the metaxenia effect on fruit development in hickory, the effects of conspecific and interspecific pollination regimes were examined in the present study. We observed the photosynthetic capacity in the peel of fruits and the related ecophysiological and morphological traits of both ph and pp fruits over a period of 120 days after pollination. Significant differences in the appearance and dry weight between ph and pp fruits were observed at 50 days after pollination (DAP). More than 70% of dry matter accumulation of the fruits was completed during 60120 DAP, while the true photosynthetic rate of the associated leaves significantly decreased by about 50% during the same period. In several cell layers of the peel, the number of chloroplasts per cell was significantly higher in pp than in ph fruits. Similarly, the ribulose 1, 5-bisphosphate carboxylase (Rubisco) activity, the total chlorophyll content, and the nitrogen content were all significantly higher in pp than in ph fruits during all growth stages; and all of these physiological quantities were positively correlated with the gross photosynthetic rate of the fruits. We conclude that the enhanced photosynthetic capacity of pp fruits contributes to their fast dry matter accumulation and oil formation. This result will provide a theoretical basis for improving hickory fruit yields in practical cultivation.